PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBASIS KEARIFAN LOKAL TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PELAJARAN IPAS - Ainun; Muhamad Ajwar; syafruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of the Contextual Teaching and Learning (CTL) model based on Nguda Kaca local wisdom on improving students' critical thinking skills in IPAS subjects at SDN 1 Tolowata. The research method used a quantitative approach with a quasi-experimental Nonequivalent Control Group Design involving 26 fourth-grade students divided into two groups. The experimental group received CTL-based learning rooted in Nguda Kaca local wisdom, while the control group used conventional teaching methods. The research instrument consisted of a critical thinking skills test covering indicators such as identifying problems, analyzing arguments, evaluating evidence, drawing conclusions, and reflecting on thoughts. The data were analyzed using a Paired Sample t-test with the help of SPSS. The results showed that the experimental group experienced an average score increase of 30.0 points (60.8%) from 49.3 to 79.3, while the control group only increased by 10.5 points (23.2%) from 45.3 to 55.8. The hypothesis test yielded a t-value of 18.456 with significance of 0.000 < 0.05, indicating a highly significant difference. An effect size of 2.84 indicates a very large effect. This study proves that the CTL learning model based on Nguda Kaca local wisdom is effective in improving students' critical thinking skills and can be used as a meaningful contextual learning alternative in the implementation of the Merdeka Curriculum.